Women’s political activity in Saudi Arabia (2000-2015) - Abdul Rahman, Sawsan Jabbar (Opción, 2020)
In recent years, the issue of women in Saudi Arabia has received considerable attention from the state and its various agencies, in order to give it a prominent role to contribute to all affairs of society. Women’s participation in all activities and aspects of society is not only a women’s interest. During the reign of King Abdullah bin Abdul Aziz, who witnessed a remarkable interest in women and their political rights, the research dealt with two topics: The first topic was to monitor the obstacles facing Saudi women in their political work. The second section was devoted to dealing with images of Saudi women in leadership positions and forms of political participation